RELASI KEBUDAYAAN PADA AJARAN AGAMA SHINTO DENGAN AGAMA ISLAM - Nurhayati, Fatikhah; Dinillah, Luthfiah; Rohmatul Jannah, Dina; Wiyono, Misun; Sobirin (Cahaya Ilmu Bangsa Institute, 2024)
This research aims to explore the cultural relationship between Shintoism and Islam. Shintoism, as a traditional Japanese religion, symbolizes unique cultural richness, while Islam, as a globally spread religion, carries universal principles that span the entire world. By using a structured and relevant literature study analysis method, this research aims to understand the cultural similarities and differences between the two and their impact on interactions between followers of the Shinto Religion and Islam. Islam and Shinto are religions that differ in the concept of teachings and beliefs of each religion. The Shinto religion is a native Japanese religion that has unique characteristics and practices in its teachings, while Islam is a religion that originates from the Arab region and has teachings and practices that are based on the Koran and hadith. Cultural relations between the Shinto religion and Islam will briefly introduce the two different religious traditions, highlighting cultural and spiritual aspects that may have points of similarity or difference. Keywords: Shinto,Relation,Islam